1986
DOI: 10.1083/jcb.103.6.2283
|View full text |Cite
|
Sign up to set email alerts
|

Chinese hamster ovary cell mutants with temperature-sensitive defects in endocytosis. I. Loss of function on shifting to the nonpermissive temperature.

Abstract: Abstract. We have isolated three independent Chinese hamster ovary cell mutants (B3853, I223, and M311) with temperature-sensitive, pleiotropic defects in receptor-mediated endocytosis. Activities affected at 41°C include uptake via the D-mannose 6-phosphate receptor, accumulation of Fe from diferric transferrin, uptake of ctz-macroglobulin, compartmentalization of newly synthesized acid hydrolases, resistance to ricin, and sensitivity to diphtheria and Pseudomonas toxins and modeccin. The three mutants also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
89
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 42 publications
(70 reference statements)
3
89
0
Order By: Relevance
“…This allows these ligands to be delivered normally to lysosomes in DTG 1-5-4 and DTF 1-5-1 (27 ; Table 11). 2 Similar results have been found with temperature-sensitive, endocytosis CHO mutants from the same complementation groups (30).…”
Section: Discussionsupporting
confidence: 76%
“…This allows these ligands to be delivered normally to lysosomes in DTG 1-5-4 and DTF 1-5-1 (27 ; Table 11). 2 Similar results have been found with temperature-sensitive, endocytosis CHO mutants from the same complementation groups (30).…”
Section: Discussionsupporting
confidence: 76%
“…2A) as expected from the temperature dependence of endocytosis (23). At the permissive temperature (34°C), net uptake of BODIPY FL-transferrin in End1 cells and wild-type cells was similar, but was strongly reduced in End1 cells upon transfer to 40°C, as expected from the known phenotype of these mutants (21). On the other hand, no difference was observed in the uptake of Spd-C 2 -BODIPY between wild-type and End1 cells at either 34 or 40°C (Fig.…”
Section: Spd-c 2 -Bodipy Uptake Does Not Require Receptor-mediated Enmentioning
confidence: 70%
“…Because a subpopulation of the PSVs could be labeled with Texas Red-transferrin, a marker of recycling endosomes, this suggested that receptor-mediated endocytosis was, at least in part, an integral part of the polyamine uptake mechanism. To address that hypothesis, we used End1 CHO mutants that are strongly defective in receptor-mediated endocytosis and exhibit pleiotropic defects at the non-permissive temperature (40°C) (21). The latter include defective ATP-dependent acidification that mainly affects early endosomes and the TGN, with late endosomes and lysosomes being largely spared (21,22).…”
Section: Determination Of Spd-c 2 -Bodipy Transport In Endocytosis-dementioning
confidence: 99%
“…The CHO mutants DTF 1-5-1 and DTG 1-5-4 obtained by Robbins and coworkers are defective in the uptake of lysosomal enzymes via the mannose-6-phosphate receptor (21,22) and have a diminished capacity to obtain iron from Tf (7; Robbins, A., personal communication). Genetic complementation has shown that DIG 1-5-4 is in the complementation group "Endl" and DTF 1-5-1 in another group "End2" (23). The characteristics of the CHO mutants suggest that they are defective in delivery of ligands to an appropriate acidic environment.…”
mentioning
confidence: 99%